Thành phần hóa học của cây rau má Centella asiatica (L.) urban thu hái tại Thành phố Hồ Chí Minh - Quỳnh Như, Võ Thị; Lộc, Trần Văn; Phương Thảo, Trần Thị; Thành, Nguyễn Tuấn; Thu Thảo, Lê Thị; Sung, Trần Văn (Vietnam Journal of Chemistry, 2016)
During the screening for biological active compounds from the medicinal plant Centella asiatica, a sample from Ho Chi Minh City has been studied. From the ethanol extract of the plant six compounds: stigmasterol, β-sitosterol, asiatic acid, madecassic acid, mixture of stigmasterol glucoside and β-sitosterol glucoside (1:1) and madecassoside have been isolated. Their structures were determined by IR, MS and NMR (1D and 2D) spectroscopy as well as by comparison with the literature data. Keywords. Centella asiatica, triterpene, triterpene glycoside, sterol.